Energy Efficient Design of Building Based on Building Information Modelling (BIM) - Giovanni Hertata Oktavian; Indradi Wijatmiko; Christin Remayanti Nainggolan; Yatnanta Padma Devia; M. Ruslin Anwar (Jurnal Mahasiswa Jurusan Teknik Sipil, 2023)
Building energy analysis is rarely carried out due to the complexity of building shape and materials. On the other hand, the urgency of environmentally friendly construction is increasing through the vision of the SDGs and Architecture 2030. The development of BIM technology is expected to provide accurate estimates of building energy consumption for projects undertaken, as well as recommendations for alternative designs and specifications to increase the energy efficiency of a building. The use of BIM technology for energy analysis during building design helps to implement green building sustainable design based on the analysis of BIM energy simulation software. Data of three-dimensional BIM model with the attributes of materials, project schedule and location are used in building energy consumption simulation analysis. Several scenarios of different materials and layout are carried out to determine the most efficient scenario for energy consumption and followed by its cost estimation. The results of this study are expected to be able to provide the energy value that can be saved through predetermined scenarios as well as the value of the costs required to run a more energy-friendly design scenario in a comprehensive manner.